L-Ascorbic Acid and α-Tocopherol Synergistically Triggers Apoptosis Inducing Antileukemic Effects of Arsenic Trioxide via Oxidative Stress in Human Acute Promyelocytic Leukemia Cells - Vineetha, Radhakrishnan Chandraprabha; Hariharan, Sreedharan; Jaleel, Abdul; Chandran, Mahesh; Nair, Raveendran Harikumaran (Frontiers in Oncology, 2020)
Chemosensitization is an effective strategy to overcome the drawbacks of arsenic trioxide (As2O3) treatment which may be possible through the use of dietary supplements in combination. The present investigation evaluates the synergistic mechanism of action of L-Ascorbic acid (L-AA) and α-Tocopherol in As2O3 chemotherapy using human leukemia (HL-60) cells as an in vitro model. In vitro assays on the cytotoxicity of As2O3 and vitamins and cellular apoptotic evidences were done; a proteomic investigation with mass spectrometry was also performed. The combination of L-AA and α-TOC potentiates As2O3 cytotoxicity in HL-60 cells, substantiated by depletion in antioxidant status, mitochondrial transmembrane potential, and inhibition of Nuclear factor erythroid 2–related factor 2 (Nrf2) and B-cell lymphoma 2 (Bcl2) transcription factors. Mass spectrometry results showed decreased expression of proteins regulating cell cycle and translation in cells treated with As2O3, L-AA and α-TOC when compared with samples treated with As2O3 alone. Many proteins associated with apoptosis and cell stress were also identified following exposure to this combination treatment. HL-60 cells became more susceptible to As2O3 in the presence of L-AA and α-TOC indicating that this combination may be a promising approach to increase the outcome of arsenic trioxide chemotherapy.